Interview with Major General (retd.) S.S. Uban on Bangladesh liberation war and secret training of Mujib Bahini, interviewed by Kabir in New Delhi - Kabir, Shahriar.
Interview with Major General (retd.) S.S. Uban on Bangladesh liberation war and secret training of Mujib Bahini, interviewed by Kabir in New Delhi.